2003
DOI: 10.1038/sj.gt.3301888
|View full text |Cite
|
Sign up to set email alerts
|

Recharging cationic DNA complexes with highly charged polyanions for in vitro and in vivo gene delivery

Abstract: The intravenous delivery of plasmid DNA complexed with either cationic lipids (CL) or polyethyleneimine (PEI) enables high levels of foreign gene expression in lung. However, these cationic DNA complexes cause substantial toxicity. The present study found that the inclusion of polyacrylic acid (pAA) with DNA/polycation and DNA/CL complexes prevented the serum inhibition of the transfection complexes in cultured cells. The mechanism mediating this increase seems to involve both particle size enlargement due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
123
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 42 publications
2
123
0
Order By: Relevance
“…45 Research has been conducted to avoid these disadvantages of polycations by using PEG 111 and polyanions. 112,113 Also, it has been reported that ionizable cationic liposome eliminates these disadvantages of polycations. 27 Kim et al 110 prepared amphiphilic NPs composed of hydrophilic poly(γ-glutamic acid) (γ-PGA) and hydrophobic L-phenylalanine.…”
Section: Disadvantages Of Delivery Systemmentioning
confidence: 99%
“…45 Research has been conducted to avoid these disadvantages of polycations by using PEG 111 and polyanions. 112,113 Also, it has been reported that ionizable cationic liposome eliminates these disadvantages of polycations. 27 Kim et al 110 prepared amphiphilic NPs composed of hydrophilic poly(γ-glutamic acid) (γ-PGA) and hydrophobic L-phenylalanine.…”
Section: Disadvantages Of Delivery Systemmentioning
confidence: 99%
“…Moreover, recharging cationic complexes with anionic compounds has been reported as a promising method to overcome the adverse effects of cationic complexes [22].…”
Section: Introductionmentioning
confidence: 99%
“…61 Therefore, it is needed to produce bio-inert hydrophilic polymers that can shield the positive surface charge in order to achieve in vivo stability. Trubetskoy et al 62 prepared ternary complexes with a negatively charged surface by adding small amount of polyanion, polyacrylic acid (PAA), to preformed pDNA/polycation complexes. These pDNA/PEI/PAA ternary complexes prevented serum inhibition for transfection in vitro and showed substantially higher gene expression in vivo than pDNA/PEI binary complexes.…”
Section: Rgd-peg-sucmentioning
confidence: 99%